Surface treatment method

By subjecting the alkoxysilane surface treatment of silica-based particulate materials to the silica-based particulate materials, the problem of insufficient compatibility with various adhesives is solved, and more stable filler performance and coloring effect is achieved.

CN119816553APending Publication Date: 2025-04-11DELTA OF SWEDEN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380055112.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-19
Filing Date
2023-07-19
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the compatibility of the silica-based particulate material with a variety of binders is insufficient, resulting in easy loss of fillers during the production and use of the composition, especially under high humidity or moisture contact conditions.

Method used

The particulate material is improved by surface treatment with at least one alkoxysilane. The process includes heating the particulate material, preparing an aqueous dispersion of alkoxysilane, mixing it with the particulate material, followed by heating and stirring to ensure a uniform coating.

Benefits of technology

Improves compatibility of particulate materials with a variety of adhesives, reduces the loss of fillers during use, reduces the amount of adhesive required under mild conditions, and achieves a stable coloring effect, avoiding pigment leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005250190770000061
    Figure BDA0005250190770000061
  • Figure BDA0005250190770000071
    Figure BDA0005250190770000071
  • Figure BDA0005250190770000141
    Figure BDA0005250190770000141
Patent Text Reader

Abstract

The present invention provides a method of coloring and surface treating the surface of a particulate material, such as a silica-based material such as sand, where the method comprises the steps of: a) optionally heating the particulate material to a temperature between 30 DEG C and 85 DEG C; b) preparing an aqueous dispersion of a colorant, an alkoxysilane, a silyl alkanoate, a polysiloxane or a mixture thereof; c0) optionally treating the particulate material; c1) mixing the dispersion prepared in step b) with the granular material in step a); c2) optionally adding an alkoxysilane, a silyl alkanoate, a polysiloxane or a mixture thereof; c3) heating the mixture to a temperature between 20 DEG C and 80 DEG C for 1 minute to 24 hours; and d) optionally mixing the sand treated in step c) with an aqueous dispersion, the aqueous dispersion being an aqueous dispersion of a colorant, an alkoxysilane, a silyl alkanoate, a polysiloxane or a mixture thereof; steps a) (e.g., use) and b) may be performed simultaneously or in either order. At least one step comprises the use of an alkoxysilane, a silyl alkanoate, and / or a polysiloxane. At least one step includes using a colorant. The aqueous dispersion of step d) may be the same as or different from the aqueous dispersion of step b); the invention also provides a colored particulate material surface-modified on at least one surface with a colorant and at least one silylalkyl or silylalkenyl group. The material may be manufactured by the method of the invention. The invention also provides a filling molding material comprising the colored particulate filler material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the surface treatment of granular materials. In particular, the present invention relates to a simple method for the surface treatment (e.g., hydrophobic surface treatment) of silica-based granular materials (e.g., sand). The present invention also relates to granular materials subjected to such surface treatment, and molding materials comprising granular materials subjected to such surface treatment and at least one binder material. Background Art

[0002] Molding compositions typically include a binder material, such as an organic polymer or silicone binder, and an inert filler material, such as a particulate mineral filler. The filler material adds bulk to the composition and alters the feel and physical properties of the composition.

[0003] When formulating filled compositions such as molding compositions, it is important to consider the compatibility of the adhesive component and the filler component. Specifically, if the adhesive's adhesion to the filler material is significantly less than the adhesive's cohesive force to itself, the filler may not be stably incorporated into the adhesive. As a result, the filler may be lost from the composition, particularly when handled or in contact with certain other materials (e.g., water).

[0004] The phenomenon of filler loss from the molding composition is generally more problematic with incompatible fillers, large filler particle sizes and / or under extreme conditions (e.g. high or low temperatures, high humidity) or in contact with solvents (e.g. moisture). This means that in some cases the type of filler and / or the conditions of use are limited due to incompatibility between filler and adhesive.

[0005] Many common fillers, such as sand, glass, silica, and many ceramics, have a high silicon dioxide (SiO2) content. They can be highly compatible with certain silicone-based adhesives, but are not always fully compatible with all adhesives, especially those based on organic polymers. This can cause difficulties during the manufacture of the composition, and / or can result in loss of adhesive during use, either in conventional use or under conditions of high humidity or contact with moisture.

[0006] In addition, filling compositions (such as molding compositions) are usually colored. Usually, the desired coloring is achieved by the coloring of the adhesive composition. If the filler material can also be colored to achieve a unique color pattern, it will be an advantage. Alternatively, it will be advantageous to color the filler material rather than the adhesive material, because the adhesive is usually used in a much lower concentration in the final filling composition. However, it is usually difficult to apply a stable colorant to the surface of the filler. For example, the resulting colored filler may leak pigment when in contact with water.

[0007] It would be a considerable advantage if a method could be found to improve the compatibility of silica-containing particulate materials with a variety of adhesives (e.g., organic polymer adhesives and / or silicone-based adhesives). It would be a further advantage if the treatment reduced the loss of filler in the filler material during use. It would be a further advantage if the treatment reduced the amount of adhesive required to effectively and / or stably coat the filler. It would be a further advantage if such a method could use mild conditions, short durations and / or mild reagents for ease of manufacture. It would be a further advantage if only a small amount (wt %) of surface treatment agent was required to improve the properties of the particulate filler. It would be a further advantage if the particulate filler could be surface treated and colored at the same time. Such coloring would advantageously be uniform and effectively fixed, with little or no leakage (e.g., during use and / or in water). Summary of the invention

[0008] The present inventors have now determined that the compatibility of particulate materials, particularly silica-based fillers, with many binders, particularly binders comprising organic polymers and / or siloxane polymers, can be improved by surface treating the particulate material with at least one alkoxysilane.

[0009] In a first aspect, the present invention provides a method for surface treating and optionally coloring at least one surface of a particulate material, the method comprising:

[0010] a) optionally heating the particulate material to a temperature between 30°C and 85°C;

[0011] b) preparing an aqueous dispersion of at least one material selected from the group consisting of a colorant, at least one alkoxysilane, at least one silylalkanoate, at least one polysiloxane, and mixtures thereof;

[0012] c1) mixing the dispersion prepared in step b) with the particulate material in step a);

[0013] c2) optionally adding at least one material selected from at least one alkoxysilane, at least one silylalkanoate, at least one polysiloxane, and mixtures thereof;

[0014] c3) heating the mixture to a temperature between 20°C and 80°C for a period between 1 minute and 24 hours; and

[0015] d) optionally mixing the treated sand formed in step c) with an aqueous dispersion of at least one colorant and / or at least one alkoxysilane and / or at least one silylalkanoate and / or at least one polysiloxane.

[0016] wherein steps a) (if used) and b) may be performed simultaneously or in either order, wherein at least one of the steps (e.g. step b), c2) and / or d) comprises the use of (e.g., the addition of) a material selected from at least one alkoxysilane, at least one silylalkanoate and / or at least one polysiloxane, and wherein the aqueous dispersion of step d) may be the same as or different from the aqueous dispersion of step b), and wherein at least one of the steps (e.g. step b), c2) and / or d) may optionally comprise a colorant.

[0017] As described herein, where the context permits, "step c" will include step c1), optional step c2), and step c3). Step c) in any method herein may include optionally treating the particulate material with an alkaline solution (e.g., an alkali metal hydroxide solution). This may be considered as an optional step c0).

[0018] Therefore, the following two descriptions can be considered equivalent:

[0019] c) mixing the dispersion prepared in step b) with the particulate material of step a) and heating the mixture to a temperature between 20°C and 80°C for a period of 1 minute to 24 hours; and

[0020] c1) mixing the dispersion prepared in step b) with the particulate material in step a); and

[0021] c3) heating the mixture to a temperature between 20°C and 80°C for a period of 1 minute to 24 hours;

[0022] In another aspect, the present invention provides a method for surface treating at least one surface of a particulate material, the method comprising:

[0023] a) optionally heating the particulate material to a temperature between ambient temperature (e.g. 20°C) and 85°C, e.g. between 30°C and 85°C;

[0024] b) preparing an aqueous dispersion of at least one alkoxysilane and / or at least one silylalkanoate; and

[0025] c) mixing the dispersion prepared in step b) with the particulate material and heating the mixture to a temperature between 20°C and 80°C for a period of 1 minute to 24 hours;

[0026] Wherein steps a) (when used) and b) may be performed simultaneously or in either order.

[0027] In the absence of heating in step a), this step consists in all suitable embodiments in obtaining a suitable particulate material.

[0028] In one embodiment, the surface treatment is a hydrophobic surface treatment.

[0029] The method of the present invention can also be used to perform surface treatment (e.g., hydrophobization) on the surface of a granular material and to color the surface thereof. Therefore, in a corresponding aspect, the present invention provides a method as described in the first aspect for simultaneously performing surface treatment and coloring on the granular material, the method further comprising:

[0030] d) mixing the treated particulate material formed in step c) with an aqueous dispersion of at least one colorant and optionally at least one alkoxysilane, at least one silylalkanoate and / or at least one polysiloxane.

[0031] According to another aspect of the present invention, coloring and surface treatment (e.g. hydrophobization) can be performed in a single step, which provides a method for coloring and surface treating at least one surface of at least one particulate material, the method comprising:

[0032] a) obtaining and optionally heating a particulate material (preferably a non-surface-modified particulate material) to a temperature between ambient temperature (e.g. 20°C) and 85°C (e.g. 30°C to 85°C);

[0033] b) preparing an aqueous dispersion of at least one alkoxysilane and / or at least one silylalkanoate and at least one colorant; and

[0034] c) mixing the dispersion prepared in step b) with the particulate material and heating the mixture to a temperature between 20 and 80° C. for a period of 1 minute to 24 hours;

[0035] Steps a) and b) may be performed simultaneously or in any order.

[0036] In another aspect, the present invention provides a method for coloring and surface treating at least one surface of at least one particulate material, the method comprising:

[0037] a) optionally heating the particulate material to a temperature between 30°C and 85°C;

[0038] b) preparing an aqueous dispersion of at least one colorant; and

[0039] c0) optionally pretreating the particulate material with an alkaline solution

[0040] c1) mixing the dispersion prepared in step b) with the granular material in step a)

[0041] c2) adding at least one material selected from at least one alkoxysilane, at least one silylalkanoate, at least one polysiloxane, and mixtures thereof; and

[0042] c3) heating the mixture to a temperature between 20°C and 80°C for a period of 1 minute to 24 hours;

[0043] Wherein steps a) (when used) and b) may be performed simultaneously or in either order.

[0044] The materials produced by the process of the present invention are very useful, particularly as fillers in combination with polymeric binders, since the surface treated particles have a high compatibility with many binders, particularly polymeric binders.

[0045] In another aspect, the present invention provides a particulate material surface-modified with at least one silylalkyl or silylalkenyl group on at least one surface. Such particulate material may also be additionally colored on at least one modified surface. Such modification and optional coloring may be performed as described herein.

[0046] In another aspect, the present invention therefore provides a particulate material having at least one treated (e.g. hydrophobized) surface formed or formable by treatment with an aqueous dispersion of at least one alkoxysilane. For all suitable aspects and embodiments of the present invention, this is typically at least one treated (e.g. hydrophobized) surface formed or formable by the methods described herein.

[0047] In another aspect, the present invention therefore provides a colored particulate material having at least one modified (e.g. hydrophobized) surface. This is preferably a surface-modified particulate material (e.g. sand) having a silica content of at least 50% by weight of the particulate material (e.g., as described herein). The colored particulate material may be or may be formed by any of the methods described herein.

[0048] In yet another aspect, the present invention provides a filled molding material comprising at least one particulate filler material and at least one polymeric binder material, wherein the particulate filler material has at least one treated (e.g., hydrophobized) surface modified with at least one silylalkyl or silylalkenyl group (and preferably also colored as described herein). Very suitable binder materials include, for example, siloxane polymers, polyesters (e.g., polycaprolactone homopolymers or copolymers), and polyvinyl acetate homopolymers or copolymers.

[0049] The molding materials of the present invention are generally hand moldable at at least one temperature between 20° C. and 45° C. The molding materials are generally not elastic. Although the molding materials can harden and become rigid materials at temperatures below, for example, 30° C. (e.g., 15° C. to 30° C.), they generally do not solidify or cure (e.g., by chemical reaction) and can be softened again and hand molded again when heated to at least one temperature between 20° C. and 45° C.

[0050] In yet another aspect, the present invention provides a method for improving the compatibility of a particulate material with a binder, the method comprising

[0051] a) optionally heating the particulate material to a temperature between 30°C and 85°C;

[0052] b) preparing an aqueous dispersion of at least one alkoxysilane and / or at least one silylalkanoate; and

[0053] c) mixing the dispersion prepared in step b) with the particulate material of step a) and heating the mixture to a temperature between 20°C and 80°C for a period of 1 minute to 24 hours;

[0054] Steps a) and b) may be performed simultaneously or in any order.

[0055] The method may include simultaneously coloring the particulate material

[0056] In a related aspect, the present invention provides a method for improving the compatibility of a particulate material with a binder while coloring the material, the method comprising:

[0057] a) optionally heating the particulate material to a temperature between 30°C and 85°C;

[0058] b) preparing an aqueous dispersion of at least one material selected from at least one alkoxysilane, at least one silylalkanoate, at least one polysiloxane and a colorant; and

[0059] c1) mixing the dispersion prepared in step b) with the particulate material in step a);

[0060] c2) optionally adding at least one material selected from at least one alkoxysilane, at least one silylalkanoate, at least one polysiloxane, and mixtures thereof;

[0061] c3) heating the mixture to a temperature between 20°C and 80°C for a period between 1 minute and 24 hours; and

[0062] d) optionally mixing the treated sand formed in step c) with an aqueous dispersion of at least one colorant and / or at least one alkoxysilane and / or at least one silylalkanoate and / or at least one polysiloxane, wherein steps a) and b) may be carried out simultaneously or in either order.

[0063] wherein at least one of the steps (e.g., steps b), c2) and / or d) comprises using a material selected from at least one alkoxysilane, at least one silylalkanoate and / or at least one polysiloxane;

[0064] wherein the aqueous dispersion of step d) may be the same as or different from the aqueous dispersion of step b); and

[0065] At least one of the steps includes a colorant.

[0066] In yet another aspect, the present invention accordingly provides a kind of filling molding material, it comprises at least one particle filler material and at least one polymer binder material, wherein the particle filler material has at least one treated (e.g., hydrophobized) surface, and the treated surface is formed or can be formed by the aqueous dispersion treatment of at least one alkoxysilane. For all suitable aspects and embodiments of the present invention, such treatment will usually produce at least one treated (e.g., hydrophobized) surface formed or can be formed by any method herein. Very suitable binder materials include, for example, siloxane polymers, polyesters (e.g., polycaprolactone homopolymers or copolymers) and polyvinyl acetate homopolymers or copolymers.

[0067] In yet another aspect, the present invention provides a filled molding material comprising at least one colored particulate filler material and at least one polymeric binder material, wherein the colored particulate filler material has at least one treated (e.g., hydrophobized) surface modified with at least one silylalkyl or silylalkenyl group and a colorant. The colored particulate filler material is preferably a material formed or formable by any method described herein in any compatible embodiment. DETAILED DESCRIPTION

[0068] Without being bound by theory, it is believed that much of the incompatibility of silica-containing fillers with binders (e.g., organic polymer binders) is a result of the filler material having a hydrophilic surface. This may, at least in part, be due to the presence of silanol (Si-OH) groups on the particle surface. This is particularly applicable to materials comprising at least one silica component, and especially particles having silica at least partially at the surface.

[0069] The inventors have now developed a method for modifying the functional groups (e.g., silanol functional groups) on the surface of a particle material so that the particle surface is modified to become more compatible with an adhesive (e.g., an organic polymer adhesive and / or a silicone polymer adhesive). In one embodiment, the modification is a hydrophobic surface modification. In a related embodiment, the particle surface becomes more hydrophobic and / or less hydrophilic than before the treatment. In a further embodiment, the surface after the treatment is more compatible with an adhesive material (e.g., an organic polymer adhesive and / or a silicone adhesive) than an untreated surface. In a further embodiment, the surface after the treatment can resist leakage of any colored pigmentation (e.g., as described herein).

[0070] All appropriate aspects of the present invention utilize at least one alkoxysilane and / or at least one silylalkanoate and / or at least one polysiloxane (preferably at least one alkoxysilane and / or at least one silylalkanoate), which is used in the form of a dispersion in a solvent. Preferably the dispersion is in an aqueous solvent, such as water (e.g. distilled or deionized water). The preparation of the alkoxysilane dispersion is step b) of the method described herein and can be performed before, after or during the heating step a) described herein. In one embodiment, a mixture of at least two alkoxysilanes and / or silylalkanoates is used. Monoalkoxysilanes or dialkoxysilanes can be used, but trialkoxysilanes form a preferred embodiment. Similarly, silylmonoalkanoates or silyldialkanoates can be used, but silyltrialkanoates form a preferred embodiment.

[0071] In one embodiment, monoalkoxysilanes and / or silylmonoalkanoates are used as silyl component in steps b) and / or d).

[0072] In one embodiment, the silanes used in the present invention may comprise, consist essentially of, or consist of monofunctional silanes (eg, monoalkoxysilanes and / or monoalkylsilanes).

[0073] In one embodiment, the silane used in the present invention may comprise, consist essentially of, or consist of a difunctional silane, such as a dialkoxysilane and / or a dialkylsilane.

[0074] In yet another embodiment, the silanes used in the present invention may comprise, consist essentially of, or consist of a mixture of monofunctional and difunctional silanes (a mixture of at least one dialkoxysilane and / or dialkylsilane with at least one monoalkoxysilane and / or monoalkylsilane).

[0075] In one embodiment of the present invention, the at least one alkoxysilane comprises i) at least one alkoxyvinylsilane and ii) at least one alkoxyalkylsilane. These may be, for example, at least one trialkoxyvinylsilane and one trialkoxyalkylsilane.

[0076] In one embodiment of the invention, the at least one alkoxysilane comprises i) at least one alkoxyvinylsilane and ii) at least one alkoxyalkylsilane, the weight ratio of i) to ii) being between 99:1 and 50:50. This can be, for example, a weight ratio of between 98:2 and 70:30, or a weight ratio of between 97:3 and 80:20.

[0077] Suitable alkoxysilanes for use in all embodiments of the present invention include silanes of the following formula i):

[0078]

[0079] in:

[0080] R1 is selected from H; CH3; C2 to C12 cyclic, branched or linear alkyl; C2 to C12 branched or linear alkenyl and mixtures thereof;

[0081] R2, R3 and R4 are each independently selected from H; CH3; C2 to C8 branched or straight chain alkyl; and mixtures thereof.

[0082] In one embodiment, R1 may be an alkenyl group, preferably a C2 to C4 hydrocarbon group having a terminal double bond. In a specific embodiment, R1 may be a vinyl group.

[0083] In another embodiment, R1 may be a linear, branched or cyclic alkyl group having 2 to 12, preferably 2 to 8 carbons. Branched hexyl or octyl groups (eg trimethylpentyl) form a preferred embodiment.

[0084] In another embodiment, R1 can be selected from H; CH3; C2 to C12 cyclic, branched or linear alkyl; C2 to C12 alkyl or alkenyl containing at least one oxygen-containing functional group (e.g., at least one ether bond and / or at least one epoxy group); and / or C5 to C10 aromatic groups, such as substituted or unsubstituted benzene rings.

[0085] In another embodiment, R1 may be selected from H; CH3; C2 to C7 cyclic, branched or linear alkyl; C2 to C7 alkyl or alkenyl containing at least one ether bond and / or at least one epoxy group.

[0086] In another embodiment, R1 may be selected from H; CH3; C2 to C7 cyclic, branched or linear alkyl; and / or at least one C5 to C7 aromatic group optionally substituted with at least one methyl and / or ethyl group.

[0087] When a moiety is described as "substituted", this will preferably be substituted with at least one CH3; C2 to C7 cyclic, branched or straight chain alkyl group.

[0088] In one embodiment, R2 to R4 can each independently be H; CH3; C2 to C6 branched or straight chain alkyl; and mixtures thereof. Methyl, ethyl and propyl are particularly suitable for R2, R3 and R4. Although each of R2 to R4 can be independently selected (including selected from the options indicated herein), in one embodiment, each of R2 to R4 can represent the same group. Therefore, in one embodiment, each of R2 to R4 can be methyl or each of R2 to R4 can be ethyl.

[0089] In a preferred embodiment applicable to any appropriate aspect of the present invention, the at least one alkoxysilane comprises i) a trialkoxyvinylsilane (e.g., a C1-C4 alkoxy group) and ii) a trialkoxytrimethylpentylsilane (e.g., a C1-C4 alkoxy group). In yet another preferred embodiment, the at least one alkoxysilane comprises i) a trimethoxyvinylsilane and ii) a triethoxytrimethylpentylsilane. The ratios of components i) and ii) discussed above apply equally to these embodiments.

[0090] In further embodiments, triethoxytrimethylpentylsilane may be present in an amount of 1 to 50 weight percent, such as 2 to 30 weight percent or 5 to 15 weight percent, of all silane compounds used in the methods and other aspects of the present invention.

[0091] In further embodiments, trimethoxyvinylsilane may be present in an amount of 50 to 99 weight percent, such as 70 to 98 weight percent or 85 to 95 weight percent, of all silane compounds used in the methods and other aspects of the present invention.

[0092] Another suitable silane material that can be used as all or part of the silane in the silane dispersion can be at least one silyl alkanoate. This can be represented by the following formula ii):

[0093]

[0094] Wherein R5 is selected from C1 to C6 alkyl, preferably methyl;

[0095] R6 and R7 are each independently selected from R9, -O-R9 and -O-CO-R9, wherein R9 is selected from H; CH3; C2 to C12 branched or linear alkyl

[0096] and R8 is selected from H; CH3; C2 to C12 cyclic, branched or linear alkyl; C2 to C12 branched or linear alkenyl and mixtures thereof;

[0097] In one embodiment, R5 is methyl or ethyl, preferably methyl.

[0098] In one embodiment, both R7 groups are -O-R9 or -O-CO-R9 groups, preferably -O-CO-R9 groups.

[0099] In one embodiment, R9 is methyl or ethyl, preferably methyl.

[0100] In one embodiment, R8 is an alkenyl group, preferably a C2 to C4 hydrocarbon group having a terminal double bond. In a specific embodiment, R8 can be a vinyl group.

[0101] The silane compound is usually used in the form of a dispersion, particularly an aqueous dispersion (e.g., in water, such as distilled or deionized water). The total silane content of the dispersion can be, for example, 0.1% to 50% by weight of the dispersion, preferably 0.5% to 30% by weight or 0.5% to 20% by weight, such as 1% to 10% by weight, 5% to 20% by weight or 5% to 15% by weight of the dispersion. Suitable dispersions can be of any effective type, including suspensions, colloidal dispersions and / or solutions.

[0102] The total weight of the silane aqueous dispersion (including the water component) is generally as small as possible while still maintaining the ability to "wet" the granular material (substantially coat its surface). In some embodiments, especially for smaller batches (e.g., less than 10 kg), the mass of the dispersion can be as high as about 5% or even 10% by mass of the granular material (e.g., sand). In other embodiments, especially for large-scale batches, such as 100 kg to 10,000 kg, the mass of the dispersion can be no more than about 0.5% or even 0.1% by mass of the granular material (e.g., sand). The inventors surprisingly found that even an amount of less than 1% by weight (e.g., 0.1% to 1%) is sufficient to substantially coat the surface of the granular material (e.g., coating greater than 75%, preferably greater than 95% of the surface).

[0103] Various aspects of the present invention are related to the surface coating of particulate materials. These materials are particularly materials containing at least one metal oxide. Typical metal oxides that constitute particulate materials (e.g., fillers) include silicon dioxide (SiO2), aluminum oxide (Al2O3), titanium dioxide (TiO2), and mixtures thereof with each other and with other minerals. Preferred particulate materials include materials with silicates and / or silicon dioxide (SiO2) as constituent minerals. In one embodiment, at least 50% by weight (e.g., 50% to 100% by weight) of the particulate material consists of SiO2 (e.g., silicon dioxide and / or silicates calculated as SiO2). This is preferably 60% to 99.9% or 70% to 95% (e.g., 75% to 90%) SiO2. In a particular embodiment, the granular material may be formed from sand having a SiO2 content of 80 to 100 wt%, preferably 85 to 100 wt%, most preferably 90 to 99.9 wt%, for example silica sand having 98.5 to 99.9 wt% SiO2. Other forms of silicon dioxide are also very suitable granular materials.

[0104] Example materials containing SiO2 include silicon dioxide (e.g., crystalline silicon dioxide, including quartz, tridymite and cristobalite, silica gel and / or fumed silica), rock (e.g., crushed stone), soda-lime glass, borosilicate glass, silica sand, quartz sand, building sand and related materials and all mixtures. Obviously, any material of controllable particle size is suitable, so, for example, "silica sand" referred to herein is used to represent silicon material having a particle size (e.g., weight average particle size or d50 size) of about 0.05 mm to 2 mm, which is a conventional particle size for sand, but particles of 0.05 mm to 0.004 mm (which may be considered "silt sand") and particles of 0.004 mm to 0.001 mm (4 μm to 1 μm) (which may be considered "clay") are also suitable for the present invention. Similarly, "pebble" sizes of 2 mm to about 10 mm can also be used. These sizes apply to all particulate materials referred to herein, not just sand. For example, the particle size of glass particles may also range from 1 μm to 10 mm, as may the particles of all other materials. However, a typical "sand" size of about 50 μm to 2 mm is very suitable. In one embodiment, the particulate material is not "nano" sized (e.g., having a particle size of 100 nm or less). In a related embodiment, the particulate material is not nano silicon dioxide. In a related embodiment, the particulate material is not nano titanium dioxide.

[0105] The particulate material may have a "bimodal" or "multimodal" size distribution. For example, the particles may include some "clay" or "silt" sized particles and some "sand" or "pebble" sized particles. This may be particularly suitable for filler applications of particulate materials because small particles can be accommodated in the gaps between larger particulate materials. In one embodiment, when there is a bimodal particle size distribution, the two peaks (maxima) in the particle size distribution curve will appear at a particle size where the larger particles are at least 2 times (e.g., 2 to 1000), preferably at least 3 times or at least 5 times larger than the smaller particles. This will contribute to the "space filling" property. The corresponding ratio can be applied to a multimodal distribution with more peaks.

[0106] In one embodiment, the particulate material is not a naturally occurring material (ie a material from a living organism), such as a plant material or an animal material. For example, the particulate material is not wood or hemp fiber.

[0107] The amount of silane used in the various methods of the invention, and therefore correspondingly present on the surface of the particulate material in the various aspects of the invention, is from about 0.01% to 1% by weight of the particulate material.

[0108] In one embodiment, the amount of silane used in the process of the invention, and accordingly the amount of silane present on the surface of the modified particles, may be in the range of about 1 mg to 200 mg of silane per square meter of particle surface area. This may be, for example, about 5 mg / m 2Up to 100 mg / m 2 or about 8 mg / m 2 Up to 70 mg / m 2 (e.g. 8 mg / m 2 Up to 35 mg / m 2 ). Corresponding calculations can be performed for each aspect and embodiment of the present invention.

[0109] In the method of the present invention, step a) includes the optional step of preheating the particulate material. This step is not necessary, but has been found to improve the method in many cases. Without being bound by theory, it is believed that this helps to remove volatiles from the surface of the material and increase the reaction rate after the addition of the silane. The particulate material can be used at ambient temperature (e.g., 20°C or higher), and generally not more than 100°C. Generally speaking, the particulate material will be heated to a temperature of 30°C to 85°C, such as 40°C to 75°C. A temperature range of 50°C to 70°C has been found to be very effective. The particulate material is preferably heated within these ranges and maintained at this temperature until ready to be contacted with the alkoxysilane dispersion. When heating is not performed, step a) simply means obtaining appropriate particulate material as required.

[0110] Part b) of the process of the invention comprises preparing an aqueous dispersion of at least one alkoxysilane in water. Silanes suitable for all aspects of the invention are discussed herein, and any suitable alkoxysilane or mixtures thereof may be used in any aspect or embodiment as is technically feasible.

[0111] The concentration of silane in the aqueous dispersion can vary over a wide range while still allowing effective surface treatment of the particulate material. For example, a silane concentration of at least 0.1% by weight in water may be effective, preferably at least 0.2% by weight or 0.5% by weight. However, concentrations up to 1% may be used, for example up to 2%, up to 2.5% or up to 5%. Higher concentrations up to 10% or up to 20% may also be suitable. It is generally preferred to use less water in larger batches, and therefore to use higher silane concentrations, because mixing may be easier and water removal is more time consuming on a larger scale.

[0112] The formation of the silane dispersion can occur before, during or after the heating step a). In one embodiment, the dispersion is formulated shortly before use to avoid degradation of the silane material in water. In one embodiment, the silane dispersion can be mixed for about 10 minutes to 180 minutes before use. This can be, for example, 20 minutes to 120 minutes or 30 minutes to 60 minutes.

[0113] In one embodiment, the silane dispersion can be prepared at a slightly acidic pH, such as pH 2 to 6, preferably pH 3 to 5, such as around pH 4. This can help reduce degradation of the silane before use. The pH can be adjusted appropriately with any suitable acid or base material, although acids such as organic acids (e.g. acetic acid) may be suitable. Adding acetic acid until the pH of the dispersion is 4±0.5 is a very suitable embodiment.

[0114] In one embodiment applicable to any compatible aspect of the present invention, the particulate material may be treated with an alkaline solution prior to surface treatment, for example with a metal hydroxide such as sodium hydroxide (e.g., NaOH (1M)). Treatment of the particulate material (i.e., sand) with an alkaline solution may provide better pigmentation fixation and water resistance. When epoxy silane is used for the surface treatment of sand, it is preferred that the sand be alkaline treated prior to silane treatment.

[0115] Mixing of the silane dispersion with the heated particulate material is step c) of the process and occurs after steps a) and b). Such mixing may be carried out at any effective temperature, but is preferably carried out at a temperature sufficient to remove moisture from the mixture, for example between ambient temperature (e.g. 20°C) and 100°C. Typically between 25°C and 80°C, such as between 40°C and 75°C (e.g. 50°C to 70°C). The mixing and heating time is generally sufficient to remove moisture from the mixture and may therefore vary widely, but is typically between about 1 minute (preferably 5 minutes) and about 24 hours, preferably between 8 minutes and 1 hour (e.g. 10 minutes to 40 minutes).

[0116] In addition to providing a surface treatment, the method of the present invention can also be used to color particulate materials. Typically, the colorant can be prepared as an aqueous solution or dispersion prior to the addition of the silane (e.g., silane dispersion) or simultaneously with the silane dispersion in step b) for mixing with the particulate filler in step c). Alternatively, an aqueous dispersion of the colorant can be added after the filler material is mixed with the silane dispersion in an additional step d). An aqueous dispersion of the colorant must be prepared and mixed with the particulate filler in at least one of steps c) or d).

[0117] In further embodiments, (e.g., when sand is not mixed with the colorant dispersion in step c)) the methods described herein may include the additional steps of:

[0118] d) mixing the treated sand formed in step c) (as described in any aspect or embodiment herein) with an aqueous dispersion of at least one colorant.

[0119] Obviously, steps c) and d) may be combined as described herein and in any technically feasible combination.

[0120] Step d) is typically followed by a heating and / or drying step to "fix" the color to the particle surface. In any embodiment, this step may use the same conditions as described herein for step c).

[0121] In all embodiments, at least one silane material (e.g., any silane material described herein or any mixture thereof) will be used in at least one step of the surface treatment method. Thus, the method can be a method for providing a silyl-treated particulate material (e.g., a colored silyl-treated particulate material).

[0122] Suitable colorants for the method of the present invention include white titanium dioxide, carbon black, organic pigments (e.g., metal complexes, nitrated, hydroxylated and / or halogenated aromatic organic molecules) and inorganic pigments of any suitable color. Many suitable colorant materials are known in the art. In one embodiment, the colorant is not titanium dioxide. In a related embodiment, the colorant does not include titanium dioxide.

[0123] In one embodiment, the colorant is not a white colorant.

[0124] In one embodiment, the colorant is not a carbon colorant. Carbon colorants include graphite, carbon black, graphene, graphene oxide, and the like.

[0125] In one embodiment, the colorant is not a black colorant.

[0126] The coloring of particulate material can be used to generate an overall colored product, or can be used to obtain a whiter or more uniformly colored particulate material to be used as a filler together with a colored or colorless binder material. Such methods can improve the color intensity of the filler material or simply be used to make the material more uniform by compensating for the color change of the starting filler particulate material. The amount of the colorant used can depend on the effect to be achieved and the intensity of the pigment, but can be, for example, 0.01% by weight to 1.5% by weight of the particulate material, such as 0.02% by weight to 0.1% by weight. For some colors, particularly black and white, a large amount of dyes may be required. In this case, 0.1% by weight to 1.5% by weight, for example 0.2% by weight to 1% by weight may be a desirable level. For other colors or the situation of black or white with lower intensity, 0.01% by weight to 0.2% by weight, for example 0.03% by weight to 0.1% by weight may be enough.

[0127] Obviously mixtures of dyes can be used, including mixtures of any suitable color combination. In one embodiment, the TiO2 pigment can be used together with another color (preferably not black) to achieve a particularly vivid effect.

[0128] As described herein, the coloring of the particulate material can be carried out in one step or two steps. When this is carried out in two steps, the aqueous dispersion of the colorant can be mixed with the silane material. This can be an alkoxysilane as described herein and / or a silyl alkanoate as described herein. Additionally or alternatively, polysiloxanes can be used, such as aminated polyalkylsiloxanes, such as poly-[3-((2-aminoethyl)amino)propyl]methyl(dimethyl)siloxane. The amount of polysiloxane can be about 0.001% to 0.1% by weight (e.g., 0.001% to 0.1% by weight) of the particulate material, and can be present in the dispersion with, for example, 0.1% to 10% by weight, such as about 1% by weight. The loss of the colored material described in any suitable aspect or embodiment herein can be "stable" to the coloring. If when 50g of colored material is contacted with 1L of water at 20°C for 5 minutes under magnetic stirring at 120rpm and allowed to settle, the water sample shows an absorbance of less than 0.5AU over a 1cm path at the visible wavelength of highest absorbance, such a material is considered to be "stable" to the loss of coloration. At the visible wavelength of highest absorbance, the absorbance over a 1cm path is preferably less than 0.3AU, more preferably less than 0.2AU or less than 0.1AU. The actual test is simple, after stirring for a few minutes, the color of the water is almost invisible to the naked eye.

[0129] The surface treated particles of the present invention are very suitable for use as fillers in molding compositions. Such compositions generally also include at least one polymer binder. Suitable binders include silicone-based binders, polyesters, polyamides and substituted aliphatic polymer binders. Specific examples include polyesters, such as polycaprolactone (optionally copolymerized with lactic acid monomers) and substituted aliphatic polymers, such as polyvinyl acetate (homopolymers or copolymers). Silicone binders include polyalkylsiloxane binders, optionally crosslinked with materials such as alkylsilyl alkanoates. The binder may optionally include boron crosslinking, but the boron content is preferably no more than 1% by weight of the binder. The binder is used to fix the filler material (i.e., particulate material, such as the particulate material described herein in any suitable aspect or embodiment) together to form a moldable material. However, even if the binder is a polysiloxane material, this is different from the surface modified material of the present invention. In a preferred embodiment, the surface modifier is covalently bonded to the surface of the particulate material (e.g., by bonding to the Si-OH groups on the surface of the silicate or silica component). Whether or not the surface modification described herein is performed, the binder preferably does not form (or substantially does not form) covalent bonds with the particulate material. Binders are typically polymeric materials that can be dissolved or melted to at least partially coat the particulate material without directly bonding to the surface. In contrast, "surface modification" as described herein, especially by silane materials, can modify the surface of a material by chemical bonds, especially covalent bonds.

[0130] In one embodiment, the binder is a thermoplastic polymer. In a related embodiment, the binder is not a curable or thermosetting polymer.

[0131] In one embodiment, the binder is not a fluorinated polymer. In one embodiment, the binder is not polytetrafluoroethane (PTFE).

[0132] In one embodiment, the binder is not a phenolic resin.

[0133] In one embodiment, the binder is not a homopolymer or copolymer of vinyl chloride and / or vinyl isobutyl ether.

[0134] It has been found that particulate material surface treated as described herein can be effectively coated with a binder using about 20% less binder material than is required to coat untreated filler. This is believed to reflect greater compatibility between the binder and the filler surface, allowing the binder to "spread" more easily on the surface.

[0135] It has also been discovered that a binder treated with a colorant can be used in conjunction with a filler material that has been treated with a colorant (eg, as described herein) to produce unique visual effects for the resulting filled molding composition.

[0136] In one embodiment, the adhesive is not an elastomer. For example, the adhesive is not (ie, does not contain more than 10%) rubber (eg, natural rubber or synthetic rubber). In another embodiment, the adhesive is not spandex. In another embodiment, the adhesive is not polyurethane.

[0137] In one embodiment, the molding material is not elastomeric. For example, if a 10 cm x 1 cm x 3 mm strip is stretched 20% at 25°C, it will break or remain stretched and will not recover to within 10% of its original length within 10 minutes at 25°C.

[0138] Adhesives typically include additional components, such as softeners and / or anti-tack agents, and may include additional components, such as pigments, glitter, mica or coated mica, fragrances, preservatives and / or flame retardants. Any combination of such additives may be used, but typically no more than 5% by weight (e.g., 0.01% to 5% by weight) of the total composition is present. Preferably, no more than 2% by weight or no more than 1% by weight.

[0139] As used herein, the terms "about", "around", "substantially" or "approximately" in connection with numbers or numerical ranges generally indicate that the specified numbers or ranges are preferred, but that such numbers may vary to a certain extent without substantially affecting the performance of the relevant materials, compositions or similar products. Those skilled in the art will generally be able to readily determine the extent to which such numbers may vary without impairing the key advantages of the invention. As a general guide, such numbers or the ends of such ranges may vary by ±10%, preferably ±5% and more preferably ±1%. A corresponding meaning may also be given to a composition "consisting essentially of" certain components, which may include up to 10%, preferably up to 5% and most preferably up to 1% of other components in addition to those specified. When a chemical group, chain or other moiety is described herein as being optionally substituted, such substitution may be absent, or one or more atoms (typically one or more hydrogen and / or carbon) in the moiety may be replaced by, for example, a halogen (e.g., F, Cl, Br, I) group, an oxy moiety (e.g., ether, alcohol, ester, carboxylic acid or epoxide), a nitrogen group (e.g., amine, amide, nitrile or nitro), or a sulfur group (e.g., thiol, disulfide, thioester, etc.). Where the context permits, up to about 10 such substitutions may be made, but typically 3 or fewer substitutions, for example 1, 2 or 3 substitutions with independently selected substituents are typical.

[0140] As used herein, "colorant" will have its natural meaning and is a material that imparts color to a material in the visible spectrum. Such colorants will typically absorb or reflect at least one wavelength in the visible spectrum (e.g., at least one wavelength between 800nm ​​and 400nm). In an optional embodiment, the colorant may have a color other than white. In another optional embodiment, the colorant may have a color other than white or black. All colored materials including processed particulate materials mentioned herein may be interpreted accordingly.

[0141] Coloring agent used herein is preferably organic or inorganic dye or pigment.In general, the amount of dye or pigment is at least 10 % by weight (e.g. 10 % by weight to 100 % by weight) of coloring agent.Coloring agent is water-soluble or water-insoluble, and can contain a certain proportion of carrier material, such as polymer.However, the amount of dye and / or pigment is at least 50 % by weight, preferably at least 70 % by weight or at least 80 % by weight in total in the preferred coloring agent.85 % by weight to 100 % by weight may be preferred.

[0142] As used herein, "molding material" refers to a material that can be manually processed at room temperature or at least one temperature between 20°C and 45°C (e.g., 20°C to 42°C or 30°C to 45°C). In one embodiment, the molding material does not solidify into a permanent shape (i.e., remains moldable) and can be re-molded under the same conditions (e.g., at a temperature between 20°C and 45°C). In one embodiment, the molding material can become rigid at a temperature below 30°C, but will remain moldable at at least one temperature between 30°C and 42°C.

[0143] In a preferred embodiment, the "molding material" is a material suitable for children to play with, particularly when the material can be contacted with water and played with underwater without any significant loss of components.

[0144] The molding material can be repeatedly shaped and reshaped. When the binder material is solid at room temperature (e.g., polyester), the molding material can be heated once or repeatedly heated and shaped until the final form is produced, at which time the composition can be cooled. Cooling can be achieved simply by leaving the 3-D shape in ambient air or cooled air (e.g., in a refrigerator or a household freezer) or by immersing it in ambient water or cooled water. Ice water will be used to "solidify" the composition of the present invention substantially immediately. Rapid solidification can also be achieved in a refrigerator or a household freezer.

[0145] In one embodiment, the molding material of any compatible aspect or embodiment of the present invention will remain moldable at a suitable temperature (e.g., 25° C. to 90° C. or 35° C. to 42° C.). The composition of the present invention preferably does not "set" or "cure". That is, the composition of the present invention does not form a rigid material that cannot be reshaped by hand at a suitable temperature (e.g., 35° C. to 42° C.). For example, the composition of the present invention will not set or cure due to a chemical reaction or due to the loss of more than 10% of the ingredients.

[0146] Example

[0147] Table 1. Raw materials used in the examples

[0148]

[0149] As used herein, d50 represents the mesh size through which 50% of the sand samples will pass. Some of the following embodiments are characterized by colored particulate filler materials. In order to test whether the coloring is stable and the particulate material does not leak, a test can be performed to evaluate the fixation of pigmentation. The test includes contacting the treated particulate material (about 2 g) with an aqueous dispersion, such as pure water (about 40 mL) or water containing a hand-washing liquid (about 0.5 mL of liquid in 40 mL of water). The resulting suspension is stirred for a few minutes (i.e., 5 minutes) using a magnetic stirring bar, and the resulting aqueous phase is then evaluated. If the aqueous phase remains almost uncolored after a few minutes, the surface modification has effectively fixed the pigmentation and prevented color leakage. Similar tests can be performed on other solvents (e.g., ethanol).

[0150] Example 1a - Surface modification of sand using appropriate amounts and mixtures of silanes

[0151] On a laboratory scale, the following procedure was used as a standard to prepare surface treated sand. The pH of the aqueous dispersion was adjusted to about 4 using acetic acid, where the silane reaction was minimal. This provided a dispersion in which the silane did not react before encountering the silanol groups on the sand particle surface and the aqueous phase was evaporated. In the first examples (1a and 1b), a dilute (5 wt%) aqueous silane solution / dispersion was used for treatment, while in example 1c the concentration of the dispersion was increased.

[0152] First prepare the silane dispersion:

[0153] - Weigh 5 g of silane. When using two or more silanes, first mix them in a beaker with a magnetic stirrer.

[0154] - Add the silane (mixture) to an aqueous solution of 94.5 g water and 0.5 g HAc (24%) under vigorous stirring to provide a solution, dispersion or coarse dispersion (depending on the silane used)

[0155] -Continue stirring (vigorous) for about 30 to 60 minutes, then contact with heated sand (see below)

[0156] Preparation of surface treated sand:

[0157] - Heat 2.5kg or 5kg of sand (as shown below) in a stainless steel pot to about 55°C to 60°C

[0158] - Add silane aqueous dispersion (100 g - about 5% silane in water) to the hot sand with continuous mixing

[0159] -Continue mixing until the water evaporates and the sand is dry

[0160] The treatment is considered complete when the sand is dry. In laboratory-scale tests, the treatment time was only a few minutes.

[0161] The properties of the treated sand are judged by bringing the sand into contact with pure water. An increase in the hydrophobicity of the particles confirms the modification. This is assessed by subjectively judging the wettability and contact angle by bringing the sand into contact with water. It is also possible to spread the sand on a flat surface and then place a drop of water on the sand. If the water stays on top of the sand in the form of a drop / lens without wetting the sand, the surface modification is considered successful. Another method is to pour the modified / treated sand into a large amount of water. If the immersed sand clumps and is not wetted by the water, or if the sand particles are very small (about 100mm or less), they may float on the water surface, then the treatment is judged to be successful. Suboptimal treatment is characterized by sand being wetted by water, not clumping, and small sand particles sinking. Table 2 lists selected experiments, showing that appropriate hydrophobic properties can be obtained by balancing the selected silane with the appropriate addition amount. Formulation D provides very good hydrophobic properties with low raw material consumption (silane to sand ratio of 0.1wt%). In the following examples, a silane mixture corresponding to Formulation D (10%wt BS1701 and 90%wt XL10) was generally used, with an addition level of 0.1%wt. The "degree of hydrophobic modification of the sand surface" was calculated from the weight of the aliphatic moieties on the particle surface, assuming that all silanes have reacted and bonded to the surface. By way of example, it is assumed that XL10 and GF62 provide vinyl groups (27 g / mol).

[0162] Table 2. Surface modification of Mam1s

[0163]

[0164] Example 1b - Surface modification of different sand qualities

[0165] Various sand masses (GA39, B15, Mamls, M32 and B55) were modified according to the above formulation D. Due to their different particle sizes, the "degree of hydrophobic modification of the sand surface" was different, although the "silane on the sand" was kept constant at 0.1% wt. The corresponding figures were d50 of about 91 microns, 130 microns, 205 microns, 270 microns and 500 microns, which translates to a "degree of hydrophobic modification of the sand surface" of 8 mg / m 2 , 11mg / m 2 , 17mg / m 2 , 23mg / m 2 and 42 mg / m 2 The latter is calculated as the weight of the aliphatic part on the particle surface, assuming that all the silane has reacted and is bound to the surface. For example, XL10 and GF62 are assumed to provide vinyl groups (27 g / mol). Silane-treated sand types are abbreviated as GA39 (ST), B15 (ST), Mam1s (ST), M32 (ST) and B55 (ST).

[0166] All sand qualities were successfully modified and the silane reaction provided hydrophobic properties to the sand as judged by the above method (see Example 1).

[0167] For M32 sand, the results will be suboptimal if the temperature is below 50°C. Therefore, M32 sand is usually heated 5°C to 10°C higher than other qualities of sand (such as Mam1s). A reasonable explanation for this observation is that it is assumed that "some contaminants" are evaporated / removed from the surface of the sand particles as the temperature increases.

[0168] Example 1c - Large scale experiment

[0169] The process time at production scale is largely determined by the time required to evaporate the water in the added silane solution / dispersion. It is therefore important to minimize the required water by increasing the concentration of the silane in the aqueous solution / dispersion without compromising the outcome of the surface treatment.

[0170] Mam1s sand was heated in a jacketed steam heated mixer to 55° C. to 60° C. The batch size on production scale was 400 kg.

[0171] A crude aqueous silane dispersion is prepared by vigorous mixing for 30 to 60 minutes. The pH is adjusted to about 4 using acetic acid, at which point the silane reacts minimally. This provides a dispersion in which the silane does not react until it encounters the silanol groups on the sand surface and the aqueous phase is evaporated.

[0172] The dispersion is then added to the preheated sand and mixing is continued until the water evaporates. The process is considered complete when the sand is dry. The process time for large-scale production is about 5 minutes to 30 minutes (depending on the amount of water used in the dispersion).

[0173] Table 3 lists the composition of the silane dispersions tested at 400 kg. The two versions of the silane dispersions were 5% wt and 11% wt, respectively. w t, the sand properties were evaluated by the above method and the results were good. Type B is recommended for large-scale production because it contains less silane (XL10 and BS1701) and water and requires less processing time. Compared with Type A, the water content is reduced by 74%, and the degree of modification is from 17mg / m 2 Reduced to 9 mg / m 2 .

[0174] Table 3a-Type A

[0175] Components 400kg batch (g) Composition (wt%) XL10 375 4.5% BS1701 42 0.5% HAc (24%) 42 0.5% water 7875 94.5% total 8334 100%

[0176] Silane / sand ratio (%) 0.10%

[0177] Water / sand ratio (%) 1.97%

[0178] Table 3b-Type B

[0179] Components 400Kg batch (g) Composition (wt%) XL10 1 88 9.9% BS1701 21 1.1% HAc (24%) 21 1.1% water 1667 87.9% total 1896 100%

[0180] Silane / sand ratio (%) 0.05%

[0181] Water / sand ratio (%) 0.42%

[0182] Example 1d - Large scale water ratio

[0183] Scale-up experiments were carried out on 400 kg batches of various sand types (GA39, Mamls, M32, B55) using Type A (see Example 1c) dispersion. All tests gave good and acceptable results. The amount added was equivalent to approximately 7.6 L of water, which had to be evaporated. It was found that evaporating 7.6 L of water took a long time, so the amount of water was reduced in subsequent tests, as shown in Table 4 below.

[0184] Despite the greatly reduced amount of water (and shorter processing time), the results did not seem to be affected.

[0185] 400kg of M32 sand was serially modified with 0.1% silane (40g BS1701 and 360g XL10) to reduce the water content. This significantly reduced the processing time required before all the water evaporated. The target starting temperature was approximately 65°C.

[0186] Table 4. Relationship between treatment time and water content

[0187]

[0188] Mam1s sand was also tested at two large scales. The water / sand ratio was reduced from 0.42% to 0.35%. The silane / sand ratios were 0.05% and 0.03%, respectively, and both concentrations showed good hydrophobic properties.

[0189] A treatment level of 0.03% can be used as a first step treatment prior to coloring. For a second step coloring treatment, the colorant / sand ratio can be 0.07% with a total addition of 0.1% silane, see Example 3 below.

[0190] Example 1e - Alternative Surface Modification Using Epoxysilane

[0191] For some silanes, such as epoxy silanes, an alternative method of surface treatment and coloring can provide better pigment fixation and water resistance. This alternative method involves treating the sand with an alkaline solution before mixing and adding the colorant before the silane.

[0192] Exemplary alternative methods of modifying the particulate filler include:

[0193] - Mamls (480 g) was treated with 5 mL of NaOH (1 M) and then allowed to stand for about 30 minutes.

[0194] - Mix Mam1s / NaOH with X-fast Blue 7080 aqueous solution (0.3 g X-fast in 5 mL water)

[0195] -Add 1.5mL of silane (GF80) and mix carefully

[0196] - Let the sand sit for about 30 minutes, then heat the sand to 80°C and stir until dry

[0197] To neutralize the NaOH, 2 mL of HCl (9%) can be added, followed by careful mixing and drying.

[0198] After standing overnight, the pigment leakage from the sand was evaluated. Sand (2 g) was contacted with excess water (40 mL) and mixed with a magnetic stir bar. Only slight leakage was observed

[0199] Example 2a - Demonstrating the Benefits of Hydrophobic Modification of Sand Fillers in Moldable Inventive Materials Prepared with Polyvinyl Acetate-Co-vinyl Laurate Binders

[0200] The adhesive was prepared by melting Vinnapas B500 / 40VL at about 100° C. The heat was turned off and then mixed with the long chain alcohol, medium chain triglycerides (Grindsted MCT 60) and triacetin were added:

[0201]

[0202] Mix the prepared binder and sand filler at about 30°C:

[0203] Binder 3.8 wt%

[0204] B55 sand or B55 sand (ST) 96.2%

[0205] Composites made with untreated B55 sand are easily reshaped by hand and are suitable for children to play with. If the material is played with in water, the sand infill tends to fall out of the matrix. This is accelerated during the drying process if the material is played with simultaneously.

[0206] The corresponding material is prepared, but using the silane-treated sand B55, B55(ST), which has similar properties in the dry state. When the material comes into contact with water, B55(ST) prevents unwanted decomposition. The material can now be used in wet conditions and played with under the water surface without significant loss of sand filler.

[0207] Example 2a(ii) - Demonstrating the benefits of hydrophobic modification of sand fillers using monofunctional silanes in moldable inventive materials prepared with polyvinyl acetate-co-vinyl laurate binders

[0208] The same binder achieves similar results when mixed with sand treated with a monofunctional silane at about 30°C:

[0209] Binder 5 wt%

[0210] Mam1s (Silane M3-ethoxylated): 95 wt%

[0211] The silane aqueous solution / dispersion was prepared following a very similar protocol to Example 1a, wherein the silane was M3-ethoxy:

[0212] -Weigh 5g of silane

[0213] - Add the silane to an aqueous solution of 94.5 g water and 0.5 g HAc (24%) under vigorous stirring to provide a solution or dispersion

[0214] -Continue (vigorous) mixing for about 30 minutes

[0215] The sand was first modified with about 0.05% silane:

[0216] - Heat 480g of Mam1s sand in a stainless steel pot to about 55°C to 60°C

[0217] - Add 5 g of silane aqueous dispersion to the hot sand with continuous mixing

[0218] -Continue mixing until the water evaporates and the sand is dry

[0219] The second step was repeated to obtain a surface modification of about 0.1% silane content on the sand.

[0220] The surface treated sand (95%) was then mixed with a polyvinyl acetate-co-vinyl laurate binder (5%) to produce a material that could be easily re-molded and used for children's play. A reference material was prepared using the same binder and sand that had not been surface modified (Mam1s). Both materials were exposed to water during play. The reference material lost most of the sand that fell out of the binder during play, while the silane M3-ethoxy modified material (Mam1s(ST)) was more stable and more resistant to water. This shows that the monofunctional silane surface treatment is also more effective in forming a moldable material that remains stable and resistant to water.

[0221] Example 2a(iii) - Demonstrating the benefits of hydrophobic modification of sand filler using epoxysilane in moldable inventive materials prepared with polyvinyl acetate-co-vinyl laurate binder

[0222] Similar effects were achieved when the epoxysilane-modified sand of Example 1e was mixed with the above-mentioned polyvinyl acetate-co-vinyl laurate binder (Example 2a(ii)) at about 30°C:

[0223] Binder 5 wt%

[0224] Mam1s (GF80 surface treated as in Example 1e): 95 wt%

[0225] Material made from sand treated with GF80 according to the method of Example 1e resisted underwater activity to a greater extent when compared to material made from untreated sand which quickly lost a large portion of its sand filler.

[0226] Example 2b - Demonstration of the Advantages of Hydrophobic Modification in Molding Materials Prepared with Polycaprolactone-Based Binders

[0227] Prepare the adhesive by melting the polymer PCL at about 70°C. Turn off the heat and then mix in Benzoflex 988:

[0228] PCL 5.4g

[0229] Benzoflex 988 9.6g

[0230] Mix the binder with sand filler (M32 sand or M32 (ST) sand) at about 50°C, and then mix with the anti-adhesive (AK10):

[0231] Adhesive 15g

[0232] M32 sand or M32 (ST) sand 84g

[0233] AK10 1g

[0234] Both compounds (based on M32 sand or silane-treated M32 (ST)) are solid at room temperature and soften at about 40°C. In the soft state, the material can be reshaped. After cooling, the material solidifies again.

[0235] When M32 sand is used as a filler, the material tends to delaminate, causing the filler to fall out of the formulation when working with warm water. Additionally, hot water is a convenient way to heat a solid material to make it ductile. Unfortunately, when using unmodified M32 sand as a filler, the delamination of the formulation is accelerated and is more noticeable when in contact with water.

[0236] By using silane-treated M32 (ST) instead of M32 sand as filler, delamination can be prevented and the material can come into contact with water without problems and without noticeable loss of filler.

[0237] Example 2c - Demonstration of the Advantages of Hydrophobic Modification in Molding Materials Prepared with Polycaprolactone-Based Binders

[0238] Similar effects were achieved when the same binder was mixed with sand treated with the monofunctional silane of Example 2a(i).The effect of silane concentration on the surface treated sand and the time of mixing the aqueous silane dispersion was evaluated.

[0239] In addition to the aqueous silane dispersion / solution (Example 2a(i)) which was stirred for 30 minutes, a solution of M3-ethoxysilane was also prepared which was stirred for only 2 minutes.

[0240] The obtained M3-ethoxysilane solution was then used to treat Mamls (480 g) at different concentrations as shown in Table '5' below:

[0241] Table '5': Summary of various concentrations of M3-ethoxysilane used to treat Mamls silica and the time required to stir the aqueous silane dispersion.

[0242] M3-ethoxysilane (%) Stirring time (Aq. dispersion) 0.1% 30 minutes 0.1% 2 minutes 0.2% 2 minutes 0.4% 2 minutes 0% n / a

[0243] Each of the treated sands in Table 5 was used to prepare a molding material with a PCL binder. A reference sample prepared with untreated Mamls was also prepared. The five materials were molded and contacted with warm water (about 40°C).

[0244] The samples prepared with untreated sand (i.e., 0% M3-ethoxysilane) immediately disintegrated and lost sand filler. The 0.1% samples prepared with the "30 minute" dispersions showed the best resistance to the challenging treatment, indicating that resistance can be improved by extending the mixing time of the aqueous dispersion. For the "2 minute" preparations, the 0.1% samples showed the lowest resistance and the 0.4% samples showed the highest resistance, indicating that higher concentrations of silane in the surface modified sand resulted in better resistance.

[0245] The examples also demonstrate that monofunctional silanes can also provide enhanced properties to the inventive materials prepared with various polymer-based binders.

[0246] Example 3a - One-step staining and fixation of X-fast

[0247] Pigments / dyes that can be stirred directly into the aqueous silane dispersion can be conveniently used. An example is BASF X-fast, which includes a number of useful color versions: e.g. Xfast Blue 7080, Xfast Green 8730, Xfast Magenta 4790, Xfast Orange 2931, Xfast Red 3860, Xfast Violet 5895, Xfast White 0025, Xfast Yellow 1256, Xfast Black 0066.

[0248] Table 6a. Composition of the final dispersion used to modify Mamls.

[0249]

[0250] In the first test, 0.5 g BS1701 and 4.5 g XL10 were dispersed in 16.25 g H2O containing 0.2 g HAc (24%), and 3.10 g X-fast was dissolved in 16.25 g H2O. The two solutions were mixed to the final composition (Table 6a), and 3.9 g was added to 480 g (unmodified) Mam1s at a temperature of about 50°C and mixed until the water evaporated. This resulted in concentrations of silane and X-fast on the sand of 0.10% and 0.062%, respectively. Extended testing of robustness involved contacting the "coated" sand with:

[0251] -water

[0252] -Melted Radiacid0406

[0253] The "coated" sand resists contact with polar and non-polar solvents without leakage. This indicates that the pigment / dye is fixed.

[0254] Table 6b lists the subjective evaluation of color intensity.

[0255] Table 6b. Maml s were stained with various X-fast versions using the above method (0.10% and 0.062% silane and X-fast on Maml s, respectively). They generally adhered firmly to the sand surface and showed little leakage into polar or monopolar liquids.

[0256] X-fast color Color Intensity 0066 black Weak to moderate 2931 orange color weak 1256 yellow medium 8730 green medium 3860 red medium 7080 blue Moderate to strong 4790 Magenta medium 5895 Purple powerful 0025 White weak

[0257] A few sand versions characterized by weaker color intensity (e.g. "orange" in Table 6b) could be successfully treated with double the amount of the same dispersion (Table 6a). Higher X-fast concentrations increased the color intensity of the treated sand.

[0258] Color intensity can also be increased without increasing the X-fast or silane concentration, but by using a two-step surface treatment procedure as suggested in Example 1d. In the first step, the sand is modified with a low level of silane (e.g. 0.03%). In the second step, the silane / sand ratio can be 0.07%, associated with a coloration corresponding to an X-fast / sand ratio of 0.062%. In total, the silane addition is 0.1% and the X-fast addition is 0.062%.

[0259] It is believed that by using a two-step procedure, all of the grits in a batch have more similar color intensity than in a one-step procedure where some grits are considered weakly colored and other grits are considered more strongly colored.

[0260] Example 3b - Two-step staining and fixation of X-fast

[0261] In the second method, the coloring step is performed after the sand has received the initial surface treatment. For the coloring (second) step, the silane HC303E was tested as a fixative for X-fast stirring in the pigment preparation. The aqueous mixture in Table 7 was prepared and mixed for about 1 hour (to allow for a reaction between HC303E and X-fast). This solution was added to Mamls (0.1% BS1701 and XL10) that had been treated with silane to a standard X-fast concentration of 0.062% (1.6 g dispersion was added to 480 g sand). Since HC303E is a 17% aqueous solution, the HC303E concentration on the sand is equivalent to about 0.0032%. The results were generally good, and the pigment appeared to be firmly retained on the surface of the sand particles, as verified by the same test procedure as above.

[0262] Table 7. HC303E is an aqueous dispersion at 17% dry weight. No additional HAc needs to be added as the dispersion is already stable. 1.6 g of this dispersion is added to 480 g of sand that has been hydrophobically modified and the water is then evaporated.

[0263] Components Weight / g Concentration / %wt X-fast 5 18.9% water 20 80.1 HC303E 1.5 1.0 total 26.5 100

[0264] Example 3c - Two-step staining and fixation of X-fast with trimethoxyphenylsilane and triacetoxy(vinyl)silane

[0265] - Evaluation of the effect of trimethoxyphenylsilane and triacetoxy(vinyl)silane (GF62) surface treatment on X-fast coloration and fixation according to a two-step process. Silane solutions / dispersions were prepared following a very similar protocol to Example 1a.

[0266] Weigh 5g silane

[0267] - Add the silane to an aqueous solution of 64 g water and 0.5 g HAc (24%) under vigorous stirring to provide a solution or dispersion

[0268] -Continue (vigorous) mixing for about 30 to 60 minutes

[0269] The surface treated sand was then prepared in a two step process. In the first step, the sand was modified with about 0.05% silane.

[0270] - Heat 480g of sand (Mamls) in a stainless steel pot to about 55°C to 60°C

[0271] - Add 3.4 g of silane aqueous dispersion to the hot sand while mixing

[0272] -Continue mixing until the water evaporates and the sand is dry

[0273] In a second step, 0.3 g of X-fast blue 7080 was dissolved in 5 g of water and mixed with another 3.4 g of silane aqueous dispersion and then added to the sand to provide a total of approximately 0.1% silane and 0.06% X-fast Mam1s relative to the weight of the sand:

[0274] - Heat the modified sand (above) in a stainless steel pot to about 55°C to 60°C

[0275] -Add the waterborne X-fast Blue 7080 / silane solution / dispersion to the hot sand with continuous mixing

[0276] -Continue mixing until the water evaporates and the sand is dry

[0277] The resulting sand had a fairly intense blue color, and there was little leakage of the pigment when the sand came into contact with excess water or ethanol during stirring with a magnetic bar.

[0278] Example 3d - Two-step staining and fixation of X-fast with M3-ethoxysilane

[0279] Sand was surface treated using an aqueous dispersion of M3-ethoxysilane from Example 2a:

[0280] - Heat 480g of sand (Mamls) in a stainless steel pot to about 55°C to 60°C

[0281] - Add 5 g of Silane M3-ethoxy dispersion to the hot sand while mixing

[0282] -Continue to mix (vigorously) until dry

[0283] A sample of X-fast blue 7080 (3 g) in water (30 g) was prepared after coloring, where 3.3 g of the resulting solution was added to hot sand and mixed until dry. Finally, another 5 g of M3-ethoxy dispersion was added to the hot sand. The resulting sand contained about 0.1% silane and about 0.06% X-fast.

[0284] After drying, it was found that the colored sand had virtually no leakage when in contact with excess water, despite vigorous stirring with a magnetic bar (2 g of sand in contact with 40 mL of water). The reference sample treated with only X-fast solution (0.06%) and no silane solution had significant leakage.

[0285] The challenge test was repeated using an aqueous solution containing water (40 mL) and hand sanitizer (0.5 mL). The difference between the monofunctional silane treated sample and the reference sample was very clear. While the silane treated sample had only very slight pigment bleed, the sand treated with X-fast Blue 7080 alone lost most of its pigmentation upon contact with the aqueous solution.

[0286] The results showed that the monofunctional silane also helped to fix the pigment on the surface of the particulate material.

[0287] Example 3e - Two-step staining and fixation of large-scale X-fast

[0288] For this experiment, while the scale was typical laboratory scale (ie 480 g sand), the silane concentration and pigment concentration were 10 times higher than the previous typical examples (ie now 1% and 0.6% compared to typical silane and pigment additions of 0.1% and 0.06%, respectively).

[0289] The silane aqueous solution of Example 3c was prepared, wherein the silane was trimethoxyphenylsilane.

[0290] - 32 g of aqueous silane solution was added to 480 g of Mamls preheated to 55-60°C.

[0291] -Continue mixing until the water evaporates and the sand is dry.

[0292] Meanwhile, 3 g of X-fast blue 7080 was dissolved in 30 g of water. This solution was mixed with the remaining 37 g of silane solution and the resulting mixture was added to the hot sand. The materials were mixed until the water evaporated and the sand was dry. The resulting surface had about 1% silane and about 0.6% X-fast blue on the sand surface.

[0293] The resulting sand was very dark in color and remained almost unchanged for several minutes when contacted with an excess of water under stirring. Wearing of the surface color layer was observed only with continued stirring, with the aqueous phase slowly turning blue.

[0294] The reference sample without silane, sand treated only with the X-fast aqueous solution, showed significant leakage, with the excess aqueous phase immediately exhibiting an intense blue color. This indicates that the surface modification process effectively fixed the pigment.

[0295] Example 4 - Viscous sand-like moldable material prepared using colored sand has less staining

[0296] Formulation "X" silicone adhesive was prepared by crosslinking 397 g of C2T with 3.5 g of ES23. The reaction occurred during mixing of the two components at a temperature of about 130°C. Crosslinking resulted in a significant increase in viscosity. The reaction was assumed to be complete after three hours.

[0297] 0.4g "X" and 1.8g CDS100 were added to a mixture of 1.2g K37 and 96g sand (described below) at a temperature of about 60°C. 0.4g HCl (9%) was added along with 0.3g Radiacid 0406, which was melted and mixed, and then 0.1g I2O was added. The last step was to add 0.2g SnS to the mixture. This formed a cohesive, sand-like moldable material that could be used for children to play with.

[0298] The sand was either the untreated Mamls or the surface treated and colored Mamls of Example 3. The coloring properties of the colored materials were subjectively evaluated. It was found that the moldable materials generally had bright colors and caused little or no staining of hands and tabletops.

[0299] Additionally, mixing the Mamls treated sand (containing trimethoxyphenylsilane or GF62) (95%) of Example 3c with the polycaprolactone binder (5%) of Example 2b resulted in a remodelable material with a deep blue color that did not stain when used. These materials were very suitable for children to play with. Thus, various silanes can be used to surface modify sand and provide enhanced properties and colored materials.

Claims

1. A method for coloring and surface treating at least one surface of a particulate material, the method comprising: a) optionally heating the particulate material to a temperature between 30°C and 85°C; b) preparing an aqueous dispersion of at least one material selected from the group consisting of a colorant, at least one alkoxysilane, at least one silylalkanoate, at least one polysiloxane, and mixtures thereof; c1) mixing the dispersion prepared in step b) with the particulate material in step a); c2) optionally adding at least one material selected from at least one alkoxysilane, at least one silylalkanoate, at least one polysiloxane, and mixtures thereof; c3) heating the mixture to a temperature between 20°C and 80°C for a period of 1 minute to 24 hours; and d) optionally mixing the treated sand formed in step c) with an aqueous dispersion of at least one colorant and / or at least one alkoxysilane and / or at least one silylalkanoate and / or at least one polysiloxane; wherein steps a) (if used) and b) may be performed simultaneously or in either order; wherein at least one step comprises using a material selected from at least one alkoxysilane, at least one silylsilane alkanoate and / or at least one polysiloxane; wherein at least one of the steps comprises the use of a colorant; and The aqueous dispersion in step d) may be the same as or different from the aqueous dispersion in step b).

2. A method for coloring and surface treating (e.g., hydrophobic surface treating) at least one surface of a particulate material, the method comprising: a) optionally heating the particulate material to a temperature between 30°C and 85°C; b) preparing an aqueous dispersion of at least one alkoxysilane and / or at least one silylalkanoate; and c) mixing the dispersion prepared in step b) with the particulate material of step a) and heating the mixture to a temperature between 20°C and 80°C for a period of 1 minute to 24 hours; wherein steps a) (if used) and b) may be performed simultaneously or in either order; and d) mixing the treated sand formed in step c) with an aqueous dispersion of at least one colorant and optionally at least one alkoxysilane, at least one silylalkanoate and / or at least one polysiloxane.

3. A method for coloring and surface treating at least one surface of at least one particulate material, the method comprising: a) optionally heating the particulate material to a temperature between 30°C and 85°C; b) preparing an aqueous dispersion of at least one alkoxysilane and / or at least one silylalkanoate; optionally at least one polysiloxane; and at least one colorant; and c) mixing the dispersion prepared in step b) with the particulate material of step a) and heating the mixture to a temperature between 20°C and 80°C for a period of 1 minute to 24 hours; Wherein steps a) (when used) and b) may be performed simultaneously or in either order.

4. A method for coloring and surface treating at least one surface of at least one particulate material, the method comprising: a) optionally heating the particulate material to a temperature between 30°C and 85°C; b) preparing an aqueous dispersion of at least one colorant; and c0) optionally pre-treating the particulate material with an alkaline solution; c1) mixing the dispersion prepared in step b) with the particulate material in step a); c2) adding at least one material selected from at least one alkoxysilane, at least one silylalkanoate, at least one polysiloxane, and mixtures thereof; and c3) heating the mixture to a temperature between 20°C and 80°C for a period of 1 minute to 24 hours; Wherein steps a) (when used) and b) may be performed simultaneously or in either order.

5. A method according to any one of the preceding claims, wherein: When present, the dispersions of step b) and step d) comprise from 0.5 to 30 wt % total silane and from 70 to 99.5 wt % water.

6. A method according to any one of the preceding claims, wherein: The weight ratio of particulate material to total silane is from 90% to 99.99% particulate material and from 0.01% to 10% total silane.

7. A method according to any one of the preceding claims, wherein: The at least one alkoxysilane comprises at least one alkoxysilane of formula I; in: R1 is selected from H; CH3; C2 to C 12 branched or straight chain alkyl; C2 to C8 branched or straight chain alkenyl; C2 to C8 containing at least one ether bond and / or at least one epoxy group 12 Alkyl or alkenyl; and / or C5 to C 10 Aromatic groups; and mixtures thereof; R2 and R4 are each independently selected from H; CH3; C2 to C8 branched or straight chain alkyl; and mixtures thereof.

8. A method according to any one of the preceding claims, wherein: The at least one silylalkanoate comprises at least one silylalkanoate of formula II; Wherein R5 is selected from C1 to C6 alkyl, preferably methyl; R6 and R7 are each independently selected from R9, -O-R9 and -O-CO-R9, wherein R9 is selected from H; CH3; C2 to C12 branched or linear alkyl; And R8 is selected from H; CH3; C2 to C12 cyclic, branched or linear alkyl; C2 to C12 branched or linear alkenyl and mixtures thereof.

9. A method according to any one of the preceding claims, wherein: The at least one alkoxysilane includes i) at least one alkoxyvinylsilane and ii) at least one alkoxyalkyl group.

10. A method according to any one of the preceding claims, wherein: The at least one alkoxysilane comprises i) at least one alkoxyvinylsilane and ii) at least one alkoxyalkylsilane, the weight ratio of i) to ii) being between 99:1 and 50:

50.

11. A method according to any one of the preceding claims, wherein: Step b) comprises: b) i) at least one alkoxyvinylsilane and ii) at least one alkoxyalkylsilane are mixed in an aqueous dispersion in a weight ratio of i) to ii) of between 99:1 and 50:

50.

12. The method according to claim 11, wherein: Step b) also includes mixing a colorant.

13. A method according to any one of the preceding claims, wherein: The at least one alkoxysilane comprises i) trimethoxyvinylsilane and ii) triethoxytrimethylpentylsilane.

14. The method according to claim 13, wherein: The content of triethoxytrimethylpentylsilane is 5 to 15 wt % of all silane compounds.

15. The method according to claim 13 or 14, wherein: The content of trimethoxyvinylsilane is 85 to 95 wt % of all silane compounds.

16. A method according to any one of the preceding claims, wherein: The particulate material comprises at least one metal oxide, such as silicon dioxide, titanium dioxide and / or aluminum oxide.

17. A method according to any one of the preceding claims, wherein: The particulate material comprises or consists of at least one selected from silicon dioxide, quartz, soda-lime glass, borosilicate glass, building sand, silica sand, quartz sand, silica gel and / or fumed silica.

18. A method for improving the compatibility of a particulate material with a binder while coloring the material, the method comprising: a) optionally heating the particulate material to a temperature between 30°C and 85°C; b) preparing an aqueous dispersion of at least one material selected from at least one alkoxysilane, at least one silylalkanoate, at least one polysiloxane and a colorant; and c1) mixing the dispersion prepared in step b) with the particulate material in step a); c2) optionally adding at least one material selected from at least one alkoxysilane, at least one silylalkanoate, at least one polysiloxane, and mixtures thereof; c3) heating the mixture to a temperature between 20°C and 80°C for a period of 1 minute to 24 hours; and d) optionally mixing the treated sand aqueous dispersion formed in step c) with an aqueous dispersion of at least one colorant and / or at least one alkoxysilane and / or at least one silylalkanoate and / or at least one polysiloxane, wherein steps a) and b) may be carried out simultaneously or in either order; wherein at least one of the steps (e.g., steps b), c2) and / or d) comprises using a material selected from at least one alkoxysilane, at least one silylalkanoate and / or at least one polysiloxane; wherein the aqueous dispersion of step d) may be the same as or different from the aqueous dispersion of step b); and At least one of the steps includes a colorant.

19. A method for improving the compatibility of a particulate material with a binder according to claim 16, comprising or consisting of a hydrophobic surface treatment according to any one of claims 1 to 15.

20. The method according to claim 18 or 19, wherein: The binder material comprises at least one polymeric material.

21. The method according to claim 20, wherein: The at least one polymer material is a polyester, a polyvinyl ester or a polysiloxane.

22. The method according to claim 21, wherein: The polyester material is polycaprolactone.

23. The method according to claim 21, wherein: The polyvinyl ester material is polyvinyl acetate.

24. A particulate material having at least one surface modified with at least one silylalkyl or silylalkenyl group and at least one colorant.

25. The granular material of claim 24, wherein The particulate material is colored on the at least one modified surface.

26. A particulate material having at least one modified (e.g. hydrophobized) surface formed or formable by treatment with an aqueous dispersion of at least one alkoxysilane, wherein: The at least one modified surface is additionally colored with a colorant.

27. A particulate material according to claim 24 having at least one modified (eg hydrophobicised) surface formed or formable by a method according to any one of claims 1 to 23.

28. A particulate material according to any one of claims 24 to 27 which is a surface modified sand having a silica content of 80 to 100 wt% and an average particle size of 0.05 to 2 mm.

29. A coloured particulate material having at least one silane-modified (eg hydrophobized) surface, preferably a surface-modified sand having a silica content of at least 50% by weight of the particulate material.

30. A coloured particulate material according to claim 29 formed or formable by treatment with an aqueous dispersion of at least one alkoxysilane and at least one colourant.

31. A coloured particulate material according to claim 29 formed or formable by a method according to any one of claims 1 to 23.

32. The colored particulate material of claim 29 having on at least one surface thereof a colorant and at least one material selected from at least one alkoxysilane, at least one silylalkanoate, at least one polysiloxane, and mixtures thereof.

33. A filled molding material comprising at least one colored particulate filler material and at least one polymeric binder material, wherein the particulate filler material has at least one treated (e.g., hydrophobized) surface modified with at least one silylalkyl or silylalkenyl group and a colorant.

34. A filled molding material comprising at least one particulate filler material and at least one polymeric binder material, wherein the particulate filler material has at least one treated (e.g., hydrophobized) surface, the treated surface being formed or formable by treatment with an aqueous dispersion of at least one alkoxysilane.

35. A filled molding material according to claim 33 or 34, wherein The particulate filler material has at least one treated surface formed or formable by the method of any one of claims 1 to 23.

36. A filled molding material according to any one of claims 33 to 35, wherein The particulate material is surface treated with an alkoxysilane at a weight ratio of 0.01% to 1% silane to particle.

37. A filled molding material according to any one of claims 33 to 36, wherein The coloured particulate filler material has at least one treated surface formed or formable by the method of any one of claims 1 to 23.